Psychometric properties of the Breast Size Rating Scale (BSRS) in Brazilian university women. (March 2019) - Junqueira, Alessandra Costa Pereira; Laus, Maria Fernanda; Sousa Almeida, Sebastião; Braga Costa, Telma Maria; da Cunha, Maria Carolina Franco; Swami, Viren
Highlights: The Breast Size Rating Scale has good psychometric properties in Brazilian women. Ratings of breast size were correlated with actual bra size and body mass index. Breast size dissatisfaction was significantly correlated with body image measures. Most women desired larger breasts than they currently had. Abstract: The present study examined the psychometric properties of a Brazilian Portuguese translation of the Breast Size Rating Scale (BSRS). A total of 194 Brazilian university women completed the BSRS along with measures of body satisfaction, body appreciation, weight discrepancy, and attitudes toward societal appearance ideals. They also had their actual bra size and body mass indices (BMIs) objectively measured. Results indicated evidence of adequate convergent validity insofar as greater breast size dissatisfaction was significantly associated with greater weight discrepancy, higher BMI, lower body appreciation, lower body satisfaction, greater use of information from society about appearance ideals, greater perceived pressure from society about appearance ideals, and greater internalisation of general and athletic appearance ideals, respectively. In our sample, 20.6% of women reported no breast size dissatisfaction, 65.5% desired a larger breast size, and 13.9% desired a smaller breast size. Findings demonstrate that BSRS scores are psychometrically sound and that breast size dissatisfaction is common among Brazilian women.